CONCEPT OF THE RESEARCH OF HIGH SCHOOL TEACHER’ PROFESSIONAL ROLES SYNERGY IN THE CONDITIONS OF THE HIGHER EDUCATION INSTITUTIONS INFORMATION AND EDUCATIONAL ENVIRONMENT - Лузік, Е.; Мельник, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The authors of the article substantiate and prospect the research professional roles synergy of modern teacher in the conditions of information and educational environment. It is determined that the synergy of the roles of the teacher will provide not only the efficiency and effectiveness of students’ educational achievements, but also, first of all, contribute to the quality assurance of higher education in the national educational space. Among the priority tasks of research authors define: to study and analyze the experience of organization and activity of services of psychological and methodological help of the teacher at the institutions of higher education; to form a normative diagnostic base for revealing the psychological peculiarities of the teacher, determining the spectrum of their roles and tendencies of professional formation during professional activity; to conduct pilot studies in order to determine the actual psychological and pedagogical problems in the conditions of technical institutions of higher education, etc. The authors propose the following stage of realization of the research’s tasks: the creation of a bank of methods for determining the socio-psychological characteristics and individual needs of the teacher; diagnostics of actual psychological and pedagogical problems of the teacher, his roles in the process of professional activity; the development and approbation of the system of pedagogical (didactic-methodical) and psychological influence on the teacher, which will provide methodical and psychological education, psychological counseling and methodical correction of the revealed negative tendencies in the professional activity of teachers. The perspective directions of the research are the diagnostics and development of criteria and indicators of synergy of professional roles of the teacher of higher technical education institution in the conditions of information and educational space. The results of the study are seen in the analytical review of the process of professional activity of the teacher in the context of integrative combination and mutual harmonization of the system; application of activity and personal approaches to deepening of scientific knowledge on psychological factors of professional activity; expanding and improving the methodological tools of research in the field of higher education psychology; development of systems of corrective influences aimed at optimization of the psychological factor of professional activity in higher technical school, etc.